(untitled) (Journal of Parents and Teachers, 2023)
The article explains the new technologies, understood as digital technologies. Thus, the author makes an exhaustive analysis of the relationship between these and the educational field. The article also includes information on the evolution of programming. In this way, it is easy to see the path of technology and its contribution to education.